Effect of freezing treatments and yeast amount on sensory and physical properties of sweet bakery products - Meziani, Smail (2012)
The frozen bakery market has grown significantly in developed countries over the past decade. Of the available preservation technologies, freezing has been recognized as an excellent method of preserving the quality characteristics of bakery products. The aim of this work was to study the influence of freezing conditions (-20, -30, -40 °C and cryogenic immersion) and yeast content on the sensory and physical properties in the final baked product (Kougelhopf). Physical parameters such as specific volume, moisture, hardness, gas cells distribution and size were determined experimentally. A sensory evaluation (appearance, color, flavor, taste, texture and overall acceptability) was performed in Kougelhopf obtained from fresh and frozen sweet doughs. The experimental results showed that high freezing rates were correlated with more extended damage, yeast activity loss and lower Kougelhopf specific volume. The freezing rate also influenced the gas cells number and size. It was shown that increasing yeast in frozen sweet doughs improved the overall quality of Kougelhopf compensating for the loss of yeast activity during the freezing process. Kougelhopf produced from sweet dough with higher yeast content (DY) presented a higher specific volume, whereas freezing rate increases its hardness. Sensory tests confirmed that experimental results were detected by panelists. © 2012 Elsevier Ltd. All rights reserved.